Pengembangan instrumen tes kemampuan berpikir kritis dan kolaborasi berpendekatan discovery learning pada materi ekosistem - Alia, Rahmah; Meiana , Nurma Alya; Mulyono , Yatin (Universitas Garut, 2025)
Development of critical thinking and collaboration test instruments with a discovery learning approach on ecosystem materials. Education plays an important role in educating and developing an individual's potential to become a useful human being. As time goes by, 21st century skills such as critical thinking and collaboration have become very important needs in the world of education. However, critical thinking skills are still a big challenge in Indonesia, with measurement results showing low scores. Therefore, learning that can improve these skills, such as Discovery Learning, is very necessary. This research aims to develop a test instrument that can measure students' critical thinking and collaboration skills on ecosystem material, using the Discovery Learning model. This research uses the Research and Development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation and evaluation. The test instrument developed includes essay questions that measure critical thinking and collaboration skills. The research results show that the instrument developed isvalid and reliable, and can measure critical thinking and collaboration skills effectively. Learning Discovery Learning on ecosystem material has been proven to improve students' critical thinking and collaboration skills, where the analysis results show a significant correlation between these two skills. This research contributes to the development of learning instruments that can be used to measure 21st century skills in the learning context in Indonesia.